Strong spin-orbit coupling inducing Autler-Townes effect in lead halide perovskite nanocrystals - Go Yumoto (Nature Portfolio, 2021)
Here, Yumoto et al. demonstrate that for a halide perovskite with large spin-orbit splitting the optical Stark effect can give way to a three level Autler-Townes effect in the near-infrared region. The multiband nature of the effect potentially allows for further optical control over quantum states.